(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Polymers used in textiles were found to be effective as actuator materials with large deformation. Particularly, the polymers with low dielectric constants used to be considered inactive to electric field were turned out to be efficient actuator materials. They were classified into three types; (1) polymer gels swollen with solvents, (2) plasticized polymers, (3) bulk polymers. From the viewpoint of easy-to-operate, polymer gel deformation with swelling and deswelling was excluded here. Swollen dielectric gels could be electrically deformed by solvent drag that induced asymmetric pressure distribution in the gels. Bending and crawling motions were observed in these materials. In the case of plasticized polymers, especially in the case of poly(vinyl chloride) with plasticizers, amoebalike reversible creep deformation was found, and the strain with over several hundreds of percent was detected. The material was stable and could have been operated for over two years. Bulk polymer film like poly(ethylene terephthalate) was found to oscillate under an application of dc electric field. Of course, the Maxwell force induced elastic contractile deformation can be expected in all cases. The variation of the electrically induced deformation in dielectric polymer materials were demonstrated to be vast and expected application fields are also spread widely, particularly as artificial muscles.